STRATEGI MUHAMMADIYAH MEMBANGUN MASYARAKAT MASA DEPAN: REFLEKSI HISTORIS- KRITIS PENDIDIKAN NASIONAL - Mukh Nursikin (Postgraduate Program Magister Pendidikan Agama Islam, 2016)
The progress of a nation depends on education. There is no developed nation without going through the educational ladder. Therefore, the challenge for developing countries such as Indonesia is how to make education a cultural strategy towards the progress of the nation. Moreover, if a country is rich in natural resources and also have qualified human resources major, then the country will certainly experience a significant leap of progress. Muhammadiyah as the strength of the nation and laying the foundations participating countries, since the beginning of his birth to take part among others in the education movement. There are several strategy in Muhammadiyah to build future society, (1) Strategy Transformation of Education because education is the process of making man as a human being who understands-nobility. (2) Strategy Moral law legal moral awareness needs to be the cornerstone of our future life. (3) Strategy Implementation of national unity. This principle reflects the character of the Indonesian nation to unite (4) Strategy social systembased society, this system departs from the recognition that anyone has the right in the field and the level of authority of each (5) constructs the basic economic strategy. Muhammadiyah demanded commitment and responsibility in implementing the strategy of building a future society to revitalize the Muhammadiyah education in order to become a strategic institution to enlighten the people and nation.